The Opioid Epidemic and the Pursuit of Moral Medicine: A Computational-Rhetorical Analysis. (January 2021) - Graham, S. Scott
This article offers a longitudinal computational-rhetorical analysis of biomedical writing on opioids. Using a corpus of 1, 467 articles and essays published in the New England Journal of Medicine and the Journal of the American Medical Association between 1959 and May 2019, this study evaluates diachronic shifts in (a) the framing of opioid pharmacology, (b) the relative attention paid to pain management versus opioid dependence risks, and (c) the distribution of statements related to physicians' primary ethical obligations. The results of these analyses largely disconfirm different current accounts of shifting physician rhetoric around opioids and pain management leading up to the recognition opioid epidemic. Most notably, the results also suggest that biomedical debates surrounding opioids are serving as proxy arguments for shifting primary bioethical obligations from individual patients to public health.